2006
DOI: 10.1111/j.1447-0756.2006.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

CA‐125 levels in ruptured and unruptured tubal ectopic pregnancies

Abstract: In intact tubal ectopic pregnancies, expectant or managed with medical treatment, the increase of CA-125 levels in the serial measurements could be a supplementary test for an early diagnosis of tubal rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
(19 reference statements)
0
11
0
1
Order By: Relevance
“…Fetal chorion, amniotic fluid and maternal decidua have been indicated as the potential sources of high serum CA-125 levels which are detected during the first trimester of pregnancy and postpartum period. This suggests disintegration of the maternal deciduas as a possible source of elevated CA125 2,3,12,13 .…”
Section: Discussionmentioning
confidence: 98%
“…Fetal chorion, amniotic fluid and maternal decidua have been indicated as the potential sources of high serum CA-125 levels which are detected during the first trimester of pregnancy and postpartum period. This suggests disintegration of the maternal deciduas as a possible source of elevated CA125 2,3,12,13 .…”
Section: Discussionmentioning
confidence: 98%
“…Predantic [11] reported that patients with abortive tubal pregnancies have signiWcantly higher serum CA-125 values compared to those with viable EPs. Malatyalioglu et al [12] found that patients with ruptured tubal pregnancies have signiWcantly higher CA-125 values than those with unruptured ones, and suggested that serum CA-125 in ruptured EPs originates not only from damaged decidual cells but also from an irritated abdominal epithelium. Madendag et al [21] also found signiWcantly higher serum CA-125 levels in subjects with ruptured as compared to unruptured tubal pregnancies.…”
Section: R P/v-hcg and The Diagnosis Of Epmentioning
confidence: 98%
“…More than 20 serum biomarkers including cancer antigen 125 (CA-125), creatinine kinase (CK), vascular endothelial growth factor, and progesterone have been examined in attempts to achieve earlier diagnosis of EP [9][10][11][12]. Although these various markers have been studied extensively in subjects with EP, conXicting Wndings have been reported such that none are currently considered appropriate for diagnostic use [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Des travaux récents ont montré l'absence d'intérêt du dosage de CA 125 pour le diagnostic de GEU [28,29]. Cependant, il semblerait qu'une augmentation du taux de CA 125 en cas de GEU soit associé au caractère rompu de celle-ci [30,31]. Cela reste cependant à confirmer.…”
Section: Ca 125unclassified